PENERAPAN TEKNIK PHOTOVOICE SEBAGAI LAYANAN BK UNTUK MENINGKAT SENSITIVITAS GENDER SISWA - Alfiandy Warih Handoyo (Universitas Sultan Ageng Tirtayasa, 2019)
AbstractThis research have purpose to improve gender sensitivity of member of photography club in SMA N 11 Yogyakarta trough photovoice technique. Researcher use action research as the research method.Gender sensitivity scale, observation, and interview is method for collectingdata. In every cycle, stary by orientating the theme, photo hunting, and ended with discuss every photothat taken by student. After 2 cycles, the photovoice technique proven be efective way to improve stident’sgender sensitivity. Before researcher start the measure, student’s gender sensitivity average is in 65,13point. In the end of 1st cycle, student’s gender sensitivity average incerase to 89, 93 point, and increase again to 96,4 point in the end of 2nd cycle.